Biogas dry reforming: Development of Ni/Na zeolite catalyst using response surface methodology approach with reaction mechanism evaluation - Abdul Hadi, Abdullah; Ahmad Zamani, Ab Halim; Amri, Mohamed; Mohd Abu Asshaary, Daud; Dabwan, Ahmed H.A. (Zibeline International Publishing, 2023)
Biogas with the composition of 60 % methane and 40 % carbon dioxide can be used as methane replacement in Dry Reforming of Methane (DRM) for high quality syngas. Endothermically nature of DRM requires an efficient catalyst to reduce the compound activation energy and change mechanism path. A nickel-based catalyst has advantages of comparable catalytic activity and abundantly available compared to a noble catalyst. However, the nickel-based catalyst has fast deactivation and sinters at higher temperature. Many factors and variables such as metals loading percentages, addition of secondary metal, support selection and promoter can affect the catalyst performance and properties. Conventionally, quest of ideal catalyst requires a lot of experiment which are time-consuming and cost-consuming. In this research, response surface methodology (RSM) approach was used to optimize the nickel-based catalyst formulation and DRM operating condition over prepared catalyst. For catalyst formulation, Box-Behken Design (BBD) was used to find the optimum ratio of nickel (1-10 %) with the use of cobalt as secondary metal (0-10 %) and magnesium as promoter (0-5 %). NaA-Zeolite synthesis from kaolin was used as support in this research. the kinetic study was carried out in order to understand the mechanism path of DRM reaction over prepared catalyst and the effect of prepared catalyst on activation energy (Ea). After conducting mathematical and statistical analysis, the result confirmed that Ni10Co9Mg1.6/NaA-Zeolite catalyst was an optimum combination that achieved 21.93 % CH4 conversion, 33.52 % CO2 conversion, 0.904 H2/CO ratio and 0.8440 stability score. The data analysis also indicated that there was an interaction effect between variables and responses. The characterization analysis was in line with the finding. Lastly, from the kinetic study, the reaction mechanism of DRM over Ni10Co9Mg1.6/NaA-Zeolite fit well with Eley-Rideal mechanism whereby CO2 was adsorbed on the catalyst surface and CH4 maintained in gas phase. The kinetic analysis also revealed that the catalyst has low activation energy for CH4 and CO2 consumptions (46.53 kJ/mol and 39.66 kJ/mol respectively). Low activation energy of CO2 indicated the involvement of RWGS reaction.